The Notorious John Morrissey : How a Bare-Knuckle Brawler Became a Congressman and Founded Saratoga Race Course - Nicholson, James C. (Book collections on Project MUSE., 2016)
An Irish immigrant, a collection agent for crime bosses, a professional boxer, and a prodigious gambler, John Morrissey was--if nothing else--an unlikely candidate to become one of the most important figures in the history of Thoroughbred racing. As a young man, he worked as a political heavy in New York before going to San Francisco in search of fortune at the height of the Gold Rush. After returning to the east coast, he was hired by Tammany Hall and was soon locked in a deadly rivalry with William Poole, better known as "Bill the Butcher." As time went on, Morrissey parlayed his youthful exploits into a remarkably successful career as a businessman and politician. After establishing a gambling house in Saratoga Springs, the hard-nosed entrepreneur organized the first Thoroughbred race meet at what would become Saratoga Race Course in 1863. Morrissey went on to be elected to two terms in the U.S. House of Representatives and two terms in the New York State Senate. In The Notorious John Morrissey, James C. Nicholson explores the improbable life of the man who brought Thoroughbred racing back to prominence in the United States. Though few of his contemporaries did more to develop the commercialization of sports in America, Morrissey's colorful background has prevented him from getting the attention he deserves. This entertaining and long-overdue biography finally does justice to his astounding rags-to-riches story while exploring an intriguing chapter in the history of horse racing.